2021
DOI: 10.1371/journal.pone.0245173
|View full text |Cite
|
Sign up to set email alerts
|

The association of cadmium and lead exposures with red cell distribution width

Abstract: Elevated red blood cell distribution width (RDW), traditionally an indicator of anemia, has now been recognized as a risk marker for cardiovascular disease incidence and mortality. Experimental and acute exposure studies suggest that cadmium and lead individually affect red blood cell production; however, associations between environmental exposures and RDW have not been explored. We evaluated relationships of environmental cadmium and lead exposures to RDW. We used data from 24,607 participants aged ≥20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Other chemical exposures may also be associated with reduced humoral responses to vaccines and could be analyzed using the NHANES dataset. 75 Several studies have documented associations in humans between a few chemicals or single chemical families and immune measure outcomes 40,59,[76][77][78][79][80] , but there has not been a broad analysis of environmental chemical exposures and immune measures in the US. Our results were based on a large, diverse, and nationally representative subset of 68,160 participants from NHANES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemical exposures may also be associated with reduced humoral responses to vaccines and could be analyzed using the NHANES dataset. 75 Several studies have documented associations in humans between a few chemicals or single chemical families and immune measure outcomes 40,59,[76][77][78][79][80] , but there has not been a broad analysis of environmental chemical exposures and immune measures in the US. Our results were based on a large, diverse, and nationally representative subset of 68,160 participants from NHANES.…”
Section: Discussionmentioning
confidence: 99%
“…32,38 Future studies may investigate the association between environmental chemicals and MCV, adjusting for intake of iron, folate, vitamin B12, and other dietary vitamins and minerals. 39,40 Associations between MCV and environmental chemicals outside of heavy metals have been under-studied and could be a new and interesting direction for research.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents may be exposed to multiple metals simultaneously through dietary or environmental sources, such as air emissions, consumer products, and contaminated drinking water (Agency for Toxic Substances and Disease Registry, 1999, 2003, 2012b, 2012a, 2020). Further, environmental metals tend to operate on similar mechanistic pathways, including reducing Fe absorption, altering heme synthesis, and disrupting erythropoietin production (McCann et al., 2020; Peters et al., 2021; Rossander‐Hultén et al., 1991), which supports the potential for metal‐metal interactions or cumulative effects. Therefore, further research is warranted to identify associations of metal mixtures with Fe status in U.S. adolescents.…”
Section: Introductionmentioning
confidence: 89%
“…Another recent study indicated that blood lead concentrations were associated with increased odds of high RDW, and these associations were more pronounced in women and those with low-to-normal MCV [9]. Moreover, lead poisoning patients have been frequently shown to display hypochromic microcytic anemia -a type of anemia in which the red blood cells (RBCs) are smaller and paler than normal, with a reduced amount of hemoglobin [10].…”
Section: Introductionmentioning
confidence: 99%